17O solid state NMR as a valuable tool for deciphering reaction mechanisms in mechanochemistry: the case study on the 17O-enrichment of hydrated Ca-pyrophosphate biominerals. (22nd September 2022) - Goldberga, Ieva; Jensen, Nicholai D.; Combes, Christèle; Mentink-Vigier, Frédéric; Wang, Xiaoling; Hung, Ivan; Gan, Zhehong; Trébosc, Julien; Métro, Thomas-Xavier; Bonhomme, Christian; Gervais, Christel; Laurencin, Danielle
Abstract : The possibility of enriching in 17 O the water molecules within hydrated biominerals belonging to the Ca-pyrophosphate family was investigated, using liquid assisted grinding (LAG) in the presence of 17 O-labelled water. Abstract : The possibility of enriching in 17 O the water molecules within hydrated biominerals belonging to the Ca-pyrophosphate family was investigated, using liquid assisted grinding (LAG) in the presence of 17 O-labelled water. Two phases with different hydration levels, namely triclinic calcium pyrophosphate dihydrate (Ca2 P2 O7 ·2H2 O, denoted t -CPPD) and monoclinic calcium pyrophosphate tetrahydrate (Ca2 P2 O7 ·4H2 O, denoted m -CPPT β) were enriched in 17 O using a "post-enrichment" strategy, in which the non-labelled precursors were ground under gentle milling conditions in the presence of stoichiometric quantities of 17 O-enriched water (introduced here in very small volumes ∼10 μL). Using high-resolution 17 O solid-state NMR (ssNMR) analyses at multiple magnetic fields, and dynamic nuclear polarisation (DNP)-enhanced 17 O NMR, it was possible to show that the labelled water molecules are mainly located at the core of the crystal structures, but that they can enter the lattice in different ways, namely by dissolution/recrystallisation or by diffusion. Overall, this work sheds light on the importance of high-resolution 17 O NMR to help decipher the different roles that water can play as a liquid-assisted grinding agent and as a reagent for 17 O-isotopic enrichment.